Out-of-pocket expenditures of Maternity Services at a Tertiary Level Hospitals in Western, Nepal - Jeevan Acharya, (Universiti Kebangsaan Malaysia, 2016)
Introduction: Government of Nepal revised free maternity health services “Aama Surakshya Karyakram” since the start of Fiscal Year 2012/13 with specifies the services to be funded, the tariffs for reimbursement and the system for claiming and reporting on free deliveries each month. This study was designed to investigate the amount of money expenditure incurred by families in using apparently free maternity services. Methods: It was a hospital based cross-sectional study conducted at Manipal Teaching Hospital and Western Regional Hospital. Nepalese women’s were not involved in the family finance and had very little knowledge of income or expenditure. That’s why face to face interviewed among 384 post-partum mothers with their husband or house head of family were conducted at the time of discharge by using a pre-tested semi-structural questionnaire. Results: The average monthly family income was 19272.4 NRs (189.01 US$). The median duration of hospital was 4 days (2-19 days). The median patient’s expenditure was equivalent to 13% of annual family income. The average total visible costs was 3887.07 NRs (38.1 US $). When the average total hidden cost 27288.5 NRs (267.6US $) was added then the average total maternity care expenditures was 31175.6 NRs (305.76 US $). Average-costper-day was 7167.5 NRs (70.29 US$). The mean patient's expenditure on the food and drinking, clothes, transport and medicine were equivalent to 53.07%, 9.8%. 7.3% and 5.6% of mean total maternity care expenditure respectively. 5963.7 NRs (58.4 US$), 7429.3 NRs (72.9 US$) and 6175.9 NRs (60.6 US$) were lost earning of women, husband and House head respondents respectively. Conclusion: A free maternity service in Nepal has high out-of-pocket expenditures and it was more than average monthly income for most families. Therefore, arrange of medicine by the hospital in the free of cost which were not included in essential drug during the hospital stay and at the discharge time. Similarly, arrange for liquid food and hot water as well as clothes for mothers and newly born baby by the hospital to enhance the hospital attendance.